2020
DOI: 10.3390/foods9010095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Systems and Ascorbate-Glutathione Cycle in Feijoa Edible Flowers at Different Flowering Stages

Abstract: Background: Feijoa (Acca sellowiana (O. Berg)) was initially introduced as an ornamental plant, but nowadays, it is widely cultivated for the numerous beneficial properties of its edible fruits. Feijoa flowers have been included in the list of edible flowers, but despite this, they are still considered niche products due to consumer skepticism and lack of publicity. Methods: This study evaluated the physicochemical traits, antioxidant system, and ascorbate-glutathione cycle in feijoa flowers at five flowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Catalase (EC 1.11.1.6) activity was assayed according to the method described by Magri et al [34] with slight modifications. The mixture for reaction containing potassium phosphate buffer (100 mM; pH 7), H 2 O 2 (20 mM) and crude enzyme extract.…”
Section: Enzyme Extraction and Activity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalase (EC 1.11.1.6) activity was assayed according to the method described by Magri et al [34] with slight modifications. The mixture for reaction containing potassium phosphate buffer (100 mM; pH 7), H 2 O 2 (20 mM) and crude enzyme extract.…”
Section: Enzyme Extraction and Activity Assaysmentioning
confidence: 99%
“…H 2 O 2 is further converted to harmless water by APX and CAT, which belong to two different classes of H 2 O 2 -scavenging enzymes with different affinities to the substrate [48]. APX reduces H 2 O 2 to H 2 O by utilizing ascorbate as an electron donor, and ascorbate is then regenerated by the ascorbate-glutathione cycle [34]. CAT activity showed the highest values at harvest and decreased in the peel and flesh of different pear cultivars/selections during storage, with higher values in flesh compared to that in peel.…”
Section: Antioxidantenzymes In Flesh and Peel Of Different Cultivar/smentioning
confidence: 99%
“…The total polyphenol content (POL) was determined by the Folin–Ciocalteu method and expressed as g of gallic acid equivalents kg −1 , whereas the total flavonoid content (FLA) was determined using the aluminum chloride colorimetric method and expressed as g of catechin equivalents kg −1 , as reported by Petriccione et al 36 . The total monomeric anthocyanins were detected spectrophotometrically as described by Magri et al 37 . and expressed as g of cyanidin‐3‐glucoside equivalents kg −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Lipoxygenase activity (EC 1.13.11) (LOX) was evaluated as described by Adiletta et al ., 37 with slight modification. Frozen powder (1:4 w/v) was homogenised in extraction buffer and LOX activity was evaluated using a reaction mix with sodium phosphate buffer (100 mmol L −1 , pH 6), linoleic acid sodium salt (5 mmol L −1 ) and crude enzyme extract (10 μL) and its activity was expressed as mmol kg −1 .…”
Section: Methodsmentioning
confidence: 99%
“…For humans, the flower petals are edible and contain, according to the variety, high concentrations of anthocyanins, flavonoids, total phenols, increased antioxidant activity and high soluble solids content (Amarante et al, 2019). Magri et al (2020) found that the petals attain the highest peak of polyphenols, anthocyanins and ascorbic acid in the F2 state, when the petals continue to open and the anthers and filaments have a dark red color, according to the BBCH scale (Ramírez & Kallarackal, 2018b).…”
Section: Introductionmentioning
confidence: 99%